Przegląd antologii serbskiej poezji współczesnej wydanych w Polsce po 1990 roku - Sobalkowska, Estera (Przekłady Literatur Słowiańskich, 2019)
This text deals with the anthologies of Serbian contemporary and newest poetry, which appeared in Poland in the last twenty-eight years. Four publications by four different authors and translators present the wealth of Serbian poetry composed by several generations of poets. Each of the anthologies presents a different image of Serbian poetry, thus showing its great diversity. Thanks to these publications, many names appeared in Poland for the first, yet not the last, time — as shown in the subsequent Bibliographies printed in the “Translation of Slavic Literatures”.